1985
DOI: 10.1063/1.96328
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Si-SiO2 interface state density on oxide thickness in structures with ultrathin (79–227 Å) oxides

Abstract: Admittance voltage characteristics of Si/79–227 Å SiO2/metal structures were measured in dark and under optical illumination in the frequency range of 30 Hz–100 kHz. For fabricating the structures, thermal oxidation was carried out in dry oxygen at 900 °C at 1 atm. The interface state versus band-gap energy profiles of the unannealed samples exhibited peaked distributions near the valence and conductance-band edges, overlying a concave background. The interface state density versus oxide thickness profile was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
2
1
0
Order By: Relevance
“…For the 1050~ samples, the effect of oxide thickness is important only when the oxide is thinner than 200/~. The general trend of thickness dependence is consistent with the measurement by Kar et al on thin (79-227A) as-grown oxides on n-type substrates, except they found that the Dit values go through a maximum around the oxide thickness of 150A, rather than varying in a monotonic fashion (10). The minor disagreement is probably due to different processing conditions and materials.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…For the 1050~ samples, the effect of oxide thickness is important only when the oxide is thinner than 200/~. The general trend of thickness dependence is consistent with the measurement by Kar et al on thin (79-227A) as-grown oxides on n-type substrates, except they found that the Dit values go through a maximum around the oxide thickness of 150A, rather than varying in a monotonic fashion (10). The minor disagreement is probably due to different processing conditions and materials.…”
Section: Resultssupporting
confidence: 89%
“…Results of the annealed samples indicate that the peak structures can be readily removed by a low temperature hydrogen annealing. Similar density peaks occurring in the lower half of bandgap have been frequently observed for as-oxidized samples (5,10,17). Employing the electron paramagnetic resonance (EPR) and quasi-static techniques, Gerardi et al observed a direct correlation between the bandgap distribution of the Pb centers and interface traps for as-grown oxides (18).…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation